Determination of the role of miR-210 AND miR-629 in regulating response towards 1'S-1'-acetoxychavicol acetate in human cervical carcinoma cells CaSki AND SiHa / Phuah Neoh Hun - Phuah, Neoh Hun (2017)
Cervical cancer is the fourth most frequent malignancy affecting women worldwide and third most common cancer among Malaysian women. Chemotherapy is one of the treatments used in treating cervical cancer patients but drug resistance and toxicities remains a major challenge. The use of natural compounds is promising because they are less toxic and able to target multiple signalling pathways. The 1'S-1'-acetoxychavicol acetate (ACA) is a natural compound isolated from wild ginger Alpinia conchigera, capable of inducing cytotoxicity in various cancer cells including cervical cancer. MicroRNAs (miRNAs) are short non-coding RNAs that regulate numerous biological processes, such as apoptosis and chemosensitivity. Past studies have reported that miR-210 and miR-629 were up-regulated in many cancers and their expressions were altered in cervical cancer cells treated with ACA and/or cisplatin. However, the functional role of miR-210 and miR-629 in regulating sensitivity towards ACA or other anti-cancer agents remains unexplored. Hence, the main aims of this study were to investigate functional role of miR-210 and miR-629 in regulating sensitivity towards ACA in cervical cancer cells, and identify the novel targets of these miRNAs. Results from reverse transcription quantitative real-time PCR (RT-qPCR) showed that ACA down-regulated the expression of miR-210 and miR-629 in both CaSki and SiHa cervical cancer cells. Data from MTT cell viability assays indicated that inhibition of miR-210 and miR-629 enhanced sensitivity towards ACA. Apoptosis assays using flow cytometric analysis for annexin V and propidium iodide dual staining and caspase 3/7 assays demonstrated that suppression of miR-210 and miR-629 induced apoptosis when the cells were treated with ACA. However, no significant changes in sensitivity towards ACA were observed when miR-210 and miR-629 were up-regulated in these cells. Bioinformatic analyses predicted mothers against decapentaplegic homolog 4 (SMAD4) and Ras suppressor-1 (RSU1) as putative novel targets of miR-210 and miR-629, respectively. The direct interactions between miRNAs and their putative targets were subsequently confirmed with luciferase reporter assays. Western blot analyses revealed that ACA up-regulated the expression of SMAD4 and RSU1 in these cervical cancer cells. Moreover, suppression of miR-210 and miR-629 also increased SMAD4 and RSU1 protein levels in these cells, respectively. MTT cell viability assays showed that ectopic expression of SMAD4 and RSU1 augmented anti-proliferative effects of ACA. Both flow cytometric analysis for annexin V and propidium iodide dual staining and caspase 3/7 assays demonstrated that over-expression of SMAD4 and RSU1 enhanced apoptosis in ACA-treated cells. In conclusion, these results demonstrated that down-regulation of miR-210 and miR-629 in cervical cancer cells conferred sensitivity towards ACA by regulating SMAD4 and RSU1. Furthermore, over-expression of SMAD4 and RSU1 augmented anti-proliferative and apoptosis-inducing effects of ACA in cervical cancer cells. Therefore, this study suggests that combinatorial treatment involving miRNAs and natural compounds could provide new strategies in treating cervical cancer.